(untitled) - Rawlley, Ratan C. (London, 1919)
The investigation on which this book is based was commenced in 1916. It is the result of personal observation and inquiry extending over a period of nearly three years, both in this country and in France. In Great Britain I devoted exclusive attention to the study of the manufacturing industry, and collected useful material from all sources, including merchants, brokers, manufacturers, and others interested in the silk industry and trade. During my tour in France I took the opportunity of making a joint economic survey of the silk producing and the silk-manufacturing industries. This joint study greatly facilitated my work, and I was thus able to discover the connecting links between the processes of production and the processes of manufacturing.
Keywords: Silk industry,Công nghiệp lụa; Great Britain,Anh